2019
DOI: 10.1128/aac.01911-18
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Campylobacter Species in a Pediatric Cohort Study

Abstract: The objective of this study was to determine the phenotypic patterns of antibiotic resistance and the epidemiology of drug-resistant Campylobacter spp. from a low-resource setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 71 publications
5
38
1
Order By: Relevance
“…When considering the phenotypic resistance, MDR was noted in 55.8% of the isolates. Simultaneously, data presented in different geographical regions showed high and extremely high prevalence of MDR among Campylobacter isolates (Schiaffino et al, 2019). Further analysis revealed that all isolates assigned to ST-257, ST-429, ST-464, ST-572, and ST-824 were associated with multiresistance.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…When considering the phenotypic resistance, MDR was noted in 55.8% of the isolates. Simultaneously, data presented in different geographical regions showed high and extremely high prevalence of MDR among Campylobacter isolates (Schiaffino et al, 2019). Further analysis revealed that all isolates assigned to ST-257, ST-429, ST-464, ST-572, and ST-824 were associated with multiresistance.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly the combination of penicillintype antibiotic (AMP, amoxicillin/clavulanic) was highly effective against Campylobacter (resistance exhibited by 2 out 43 isolates, CI 95%: 1.3-15.5%).No resistance to amoxicillin-clavulanic acid was detected by Post et al (2017) in Belgium and Wallace et al (2019) in Australia in clinical isolates. Also, the study conducted by Schiaffino et al (2019) provides compelling evidence to propose amoxicillin/clavulanic acid as an effective treatment for campylobacteriosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples collected as part of a cohort study from Iquitos, in the Peruvian Amazon, between 2002 and 2006. In this age-stratified sample set of 442 children aged 0-5 years [7,[13][14][15]41,42], children were visited 3 times weekly to form a continuous symptom history of childhood illnesses. Stool samples were collected quarterly from all children and in cases in which diarrhea was detected (92.3% of episodes detected by surveillance had a sample collected;…”
Section: Sampling and Cohort Informationmentioning
confidence: 99%
“…However, in severe cases, antibiotics such as ciprofloxacin, tetracycline and erythromycin can be prescribed [6]. However, the efficiency of antibiotics against Campylobacter infections is decreasing due to an increase in antibiotic resistance [7]. The use of antibiotics in poultry production may contribute to the emergence of resistant strains in human through the food chain [8].…”
Section: Introductionmentioning
confidence: 99%